Defining disease modification in myelofibrosis in the era of targeted therapy. Issue 13 (2nd May 2022) - Pemmaraju, Naveen; Verstovsek, Srdan; Mesa, Ruben; Gupta, Vikas; Garcia, Jacqueline S.; Scandura, Joseph M.; Oh, Stephen T.; Passamonti, Francesco; Döhner, Konstanze; Mead, Adam J.
Abstract : The development of targeted therapies for the treatment of myelofibrosis highlights a unique issue in a field that has historically relied on symptom relief, rather than survival benefit or modification of disease course, as key response criteria. There is, therefore, a need to understand what constitutes disease modification of myelofibrosis to advance appropriate drug development and therapeutic pathways. Here, the authors discuss recent clinical trial data of agents in development and dissect the potential for novel end points to act as disease modifying parameters. Using the rationale garnered from latest clinical and scientific evidence, the authors propose a definition of disease modification in myelofibrosis. With improved overall survival a critical outcome, alongside the normalization of hematopoiesis and improvement in bone marrow fibrosis, there will be an increasing need for surrogate measures of survival for use in the early stages of trials. As such, the design of future clinical trials will require re‐evaluation and updating to incorporate informative parameters and end points with standardized definitions and methodologies. Abstract : There is a need to understand and define disease modification in myelofibrosis. This review examines the latest clinical data of targeted therapies for myelofibrosis and proposes a definition of disease modification.